Dexmedetomidine Use in Infants Undergoing Cooling Due to Neonatal Encephalopathy (DICE Trial): A Randomized Controlled Trial: Background, Aims and Study Protocol - Baserga, Mariana; DuPont, Tara L.; Ostrander, Betsy; Minton, Stephen; Sheffield, Mark; Balch, Alfred H.; Bahr, Timothy M.; Watt, Kevin M. (Frontiers in Pain Research, 2021)
Background Neonatal hypoxia-ischemia encephalopathy (HIE) is the leading cause of neonatal death and poor neurodevelopmental outcomes worldwide. Therapeutic hypothermia (TH), while beneficial, still leaves many HIE treated infants with lifelong disabilities. Furthermore, infants undergoing TH often require treatment for pain and agitation which may lead to further brain injury. For instance, morphine use in animal models has been shown to induce neuronal apoptosis. Dexmedetomidine is a potent α2-adrenergic receptor agonist that may be a better alternative to morphine for newborns with HIE treated with TH. Dexmedetomidine provides sedation, analgesia, and prevents shivering but does not suppress ventilation. Importantly, there is increasing evidence that dexmedetomidine has neuroprotective properties. Even though there are limited data on pharmacokinetics (PK), safety and efficacy of dexmedetomidine in infants with HIE, it has been increasingly administered in many centers. Objectives To review the current approach to treatment of pain, sedation and shivering in infants with HIE undergoing TH, and to describe a new phase II safety and pharmacokinetics randomized controlled trial that proposes the use of dexmedetomidine versus morphine in this population. Methods This article presents an overview of the current management of pain and sedation in critically ill infants diagnosed with HIE and undergoing TH for 72 hours. The article describes the design and methodology of a randomized, controlled, unmasked multicenter trial of dexmedetomidine versus morphine administration enrolling 50 (25 per arm) neonates ≥36 weeks of gestation with moderate or severe HIE undergoing TH and that require pain/sedation treatment. Results and Conclusions Dexmedetomidine may be a better alternative to morphine for the treatment of pain and sedation in newborns with HIE treated with TH. There is increasing evidence that dexmedetomidine has neuroprotective properties in several preclinical studies of injury models including ischemia-reperfusion, inflammation, and traumatic brain injury. The Dexmedetomidine Use in Infants undergoing Cooling due to Neonatal Encephalopathy (DICE) trial will evaluate whether administration of dexmedetomidine versus morphine is safe, establish dexmedetomidine optimal dosing by collecting opportunistic PK data, and obtain preliminary neurodevelopmental data to inform a large Phase III efficacy trial with long term neurodevelopment impairment as the primary outcome.